A survey of improved gari frying methods - Samuel, T.M.; Igbeka, J.C.; Kolawole, O.P. (Walter de Gruyter GmbH, 2010)
Processing cassava to gari is a storage method. Gari frying is the last operation and is still largely done manually in Nigeria. The women processors usually adopt various postures during production as appeared comfortable to them. This paper reports the survey carried out in 50 gari factories across five states (Ekiti, Ondo, Ogun, Osun and Oyo) of southwestern Nigeria and the versions of Improved Traditional Garification Methods (ITGMs) in use. These were grouped into eight (ITGM I-VIII) based on operator's and workplace's characteristics, heating process and estimated output. Their modes of operation were explained and estimation of their outputs and common working postures were determined. Four working postures were identified namely, sitting beside (SB), sitting in front (SF), alternating between sitting and standing (ASS) and standing (S). ITGM VIII with operator in standing posture using both hands had the highest output, having efficient use of both hands and indicating an ergonomic balance of right and left arms as well as overcoming certain asymmetric symptoms in the workers. ITGM VIII is, therefore, recommended based on output.